THU0461-HPR Global assessment of disease by the patient in the new ACR/EULAR remission criteria: Why do not fulfil the remission?. (23rd January 2014) - Sanchez, S.; Iniesta, S.; Lisbona, M.P.; Pàmies, A.; Almirall, M.; Maymo, J.; Carbonell, J.
Abstract : Background: Recently, new criteria has been described for assessing Rheumatoid Arthritis (RA) remission. However, in clinical practice, patients who may be in remission by these criteria (ACR/EULAR 2011), ofter fail to meet patient's global assessment (PtGA) scale of 0 to 10 with a value less than or equal to 1. Objectives: To evaluate in patients with rheumatoid arthritis (RA), the reasons for non compliance with the new remission criteria ACR/EULAR due to a high PtGA and not related to the activity of the RA. Methods: We included consecutively from April to December 2011 all patients with RA in remission for the composite index of activity, simplified disease activity index (SDAI) ≤3.3 and swollen joint count (SJC) ≤1, tender joint count (TJC) ≤1, C-reactive protein (CRP) ≤1 mg/dl but with PtGA >1 cm. Demographic variables (date of birth, sex, educational level), disease (date of diagnosis of RA, presence of radiological erosions, serum levels of RF and ACPA), activity DAS28, VAS pain (0-10 cm), PtGA (0-10 cm), functional disability by HAQ, treatment (corticosteroids, DMARDs and/or tumor necrosis factor (anti-TNF), and comorbidity not associated with RA as possible causes of a PtGA>1 cm. Data were analyzed with SPSS v.15. Results: 55 patients (87.3% women) with a mean age of 57.8±12.7 years and a mean disease duration of 4.2±3.1 years were included. 60% were seropositive for rheumatoid factor (RF), 61.8% for Anti-citrullinated protein antibodies (ACPA) and 87.3% had radiographic erosions. 20% of patients had basic studiesand only 16.4% medium-high level. The mean HAQ was 0.483±0.387. 80% were treated with DMARDs (47.3% methotrexate), a 34.5% anti-TNF with or whithout DMARDs, 52.8% were taken corticosteroids (mean dose to prednisone equivalent of 2.1±2.2 mg per day). The mean DAS28 was 2.3±0.5, the pain VAS 3.6±1.8 cm and 3.7 ± PtGA was 1.2 cm. Acute phase reactants were both below normal level (ESR=16.5±14.7 (normal <37 mm/h) and CRP=0.3±0.2 (normal <0.8mg/dl). The reasons why patients considered to be in remission (new ACR/EULAR criteria) did not meet a PtGA ≤1 cm is shown in Table 1 . Conclusions: In our series, 65.5% of the patients on remission by other components if the new ACR/EULAR criteria, reported a PtGA >1 cm due to a non-RA joint disease, osteoarthritis and soft tissue rheumatism being most prevalent disorders. The Rheumatology nurse should ensure proper completion of visual analog scales especially the PtGA in patients with RA as it is an important variable in the index of activity and remission of the disease. Disclosure of Interest: None Declared